Effects of menthone and piperitone on growth, chlorophyll a and β-carotene production in Dunaliella salina - Mina Zarei, Mohammad Ali Mobasher, Mohammad Hossein Morowvat, Pegah Mousavi, Nima MontazeriNajafabady, Nasim Hajighahramani, Younes Ghasemi (Journal of Applied Pharmaceutical Science, 2016)
Recently, studying essential oils and secondary metabolites of plants and microalgae have received much attention. The biosynthesis of the secondary metabolites is strongly influenced by different environmental factors. Monoterpenes as a main fraction of essential oils of fruits and vegetables have many clinical applications. They could inhibit the carcinogenesis processes and therefore might be effective in treatment of cancers. Dunaliella salina, a photosynthetic green microalga is known as a rich source for β-carotene production. In this study, the effects of some monoterpenes including menthone and piperitone was investigated on yield of production of β-carotene were studied. Menthone and piperitone as parameters of stress can make tensions to the medium of D. salina increasing its β-carotene and chlorophyll a content in every single cell but on the other hand these two monoterpenes cause a decrease in the concentration of β-carotene and chlorophyll a.
Keywords: Dunaliella salina, monoterpenes, menthone, piperitone, chlorophyll a,&beta; -carotene.